Market Chain Analysis of High Value Fruits in Multan Region - Chaudhary, Abdul Haseeb (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
This research aimed at assessing the market chain of banana, avocado and mango fruits in Multan zone. Both primary and secondary data were collected from 2 purposively selected fruits producing districts namely North Multan and South Multan areas. Primary data were collected through semi-structured questionnaire and focus group discussion. A total of 150 households were selected by using systematic random sampling technique. In addition, 40 traders were selected by using simple random sampling technique. Market structure-conduct-performance analysis model was used to assess the performance of the fruits market. The result revealed that the participants in the fruits markets were identified as primary actors and secondary actors. Primary actors in the fruits market chain were producers, brokers/agents/, farmer traders, collectors, and wholesalers. Whereas, local tax authority, local police, transporters, and district Trade and Industry office were identified as secondary actors. Fruits market in the area was characterized by non-competitive nature with concentration ratio ranging from 42 to 91.10% indicating the existence of oligopoly market structure. Entrance and exit in the fruits market was blocked by licensing and access to channel. A channel that links producers to local wholesalers through brokers was more efficient in terms of large volumes of sales. However, performance of the fruits market was affected by seasonality, the existence of few big traders, limited access to information, absence of organized market center and brokers’ interference. Therefore, attention must be given to alleviate the problems to improve the performance of the fruits market.